Ownership and Pay in Britain. (12th May 2017) - Pendleton, Andrew; Bryson, Alex; Gospel, Howard
Abstract: Drawing on principal–agent perspectives on corporate governance, the article examines whether employees' hourly pay is related to ownership dispersion. Using linked employee‐workplace data from the British Workplace Employment Relations Survey 2011, and using a variety of techniques including interval regression and propensity score matching, average hourly pay is found to be higher in dispersed ownership workplaces. The premium is broadly constant across most of the wage distribution, but falls at the 95th percentile to become statistically non‐significant. This contrasts with earlier papers which indicate that higher level employees are the primary beneficiaries of higher pay from dispersed ownership. The dispersed ownership pay premium is not readily explained by efficiency wage perspectives but is consistent with a managerial desire for a 'quiet life'.